Alginate-Based 3D A549 Cell Culture Model to Study Paracoccidioides Infection - dos Santos, Kelvin Sousa [UNESP]; Oliveira, Lariane Teodoro [UNESP]; de Lima Fontes, Marina [UNESP]; Migliato, Ketylin Fernanda; Fusco-Almeida, Ana Marisa [UNESP]; Mendes Giannini, Maria José Soares [UNESP]; Moroz, Andrei [UNESP] (MDPI, 2023)
A three-dimensional (3D) lung aggregate model based on sodium alginate scaffolds was developed to study the interactions between Paracoccidioides brasiliensis (Pb) and lung epithelial cells. The suitability of the 3D aggregate as an infection model was examined using cell viability (cytotoxicity), metabolic activity, and proliferation assays. Several studies exemplify the similarity between 3D cell cultures and living organisms, which can generate complementary data due to the greater complexity observed in these designed models, compared to 2D cell cultures. A 3D cell culture system of human A549 lung cell line plus sodium alginate was used to create the scaffolds that were infected with Pb18. Our results showed low cytotoxicity, evidence of increased cell density (indicative of cell proliferation), and the maintenance of cell viability for seven days. The confocal analysis revealed viable yeast within the 3D scaffold, as demonstrated in the solid BHI Agar medium cultivation. Moreover, when ECM proteins were added to the alginate scaffolds, the number of retrieved fungi was significantly higher. Our results highlight that this 3D model may be promising for in vitro studies of host–pathogen interactions.
Keywords: 3D culture; fungi infection; scaffolds; sodium alginate